AUGMENTED REALITY (AR) SEBAGAI MEDIA PEMBELAJARAN PERKENALAN HEWAN PURBAKALA DINOSAURUS - Mina Ismu Rahayu; Ilham Doni Waluya; Faiqunisa Faiqunisa (JURTIK:Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2022)
ABSTRACT Currently, children know dinosaurs ancient animals only through a book, pictures and skeletons in museums, so children have to use their imagination to imagine the shape of dinosaurs but using augmented reality (AR) technology is expected in their learning about the but introduction of ancient animalsdinosaurs can be more interesting and fun because AR can be a visualization tool for ancient animals in 3D.So that it can make it easier for children to get information about ancient dinosaurs from shape, type, movement, to sound. In this application, the visualization model of ancient dinosaurs that has been given a marker will be detected by the system as a marker, the detection uses a pattern recognition method, namely the Natural Feature Tracking (NFT) method found in the Qualcomm Vuforia Library. Therefore, with this application, children can learn ancient dinosaurs more easily and interestingly, because the delivery of information in 3D from augmented reality can increase children's enthusiasm in the learning process to get to know dinosaurs ancient animals. Keywords: Augmented Reality, Natural Feature Tracking, Ancient Animals, Dinosaur, Unity3D, Vuforia.